2000
DOI: 10.1002/(sici)1096-8652(200006)64:2<107::aid-ajh6>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection and lymphoproliferative diseases in France: A national study

Abstract: The putative role of hepatitis C virus (HCV) infection in the pathophysiology of lympho-proliferative diseases (LPD) is supported by North American and southern European studies reporting high HCV seroprevalence in patients with B-cell-non-Hodgkin lym-phoma (NHL). In order to evaluate the situation in France, we conducted a retrospective national study about the association of chronic HCV infection and LPD. 72 Internal Medicine and Infectious Diseases departments were contacted. Response rate was 51.4%. We rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 30 publications
(55 reference statements)
3
22
0
Order By: Relevance
“…[36][37][38] In contrast, our results were comparable with the 9% to 42% HCV prevalence rate found in other studies [8][9][10][11] and suggest a potential pathogenic role of HCV infection in primary hepatic lymphoma. This finding was previously suspected in several case reports of PLL occurring in HCV positive patients.…”
Section: Discussionsupporting
confidence: 88%
“…[36][37][38] In contrast, our results were comparable with the 9% to 42% HCV prevalence rate found in other studies [8][9][10][11] and suggest a potential pathogenic role of HCV infection in primary hepatic lymphoma. This finding was previously suspected in several case reports of PLL occurring in HCV positive patients.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, lymphadenopathy was seen in 22 of the 136 HCV patients (16.2%), with a higher prevalence in cryoglobulinpositive than in cryoglobulin-negative patients (35.3% vs 4.7%, OR 11.0, 95% CI 3.4-35.1). Epidemiological studies have confirmed a link between HCV infection and B-cell non Hodgkin's lymphoma [61][62][63] . In a recent meta-analysis, the prevalence of HCV infection in patients with B-cell non Hodgkin's lymphoma was approximately 15%, which is much higher than the prevalence of HCV in the general population [64] .…”
Section: Discussionmentioning
confidence: 95%
“…A significant association between B-cell derived NHL and HCV infection was initially reported in Italian subjects [43][44][45][46][47][48][49] , and subsequently confirmed by a large majority of international studies [33,42,47,[50][51][52][53][54] . However, discordant data appeared in northern European and North American surveys [55][56][57][58][59][60] , and it is now evident that a clear south/north gradient of prevalence exists, in part reflecting different HCV infection prevalence in the general population, and suggesting the contribution of environmental and/or genetic factors [54] . From a histopathological point of view, although all histological types can virtually be found, B-cell derived NHL is the most common of the HCV-related lymphatic malignancies [33,45,47,48,[61][62][63][64] .…”
Section: Mixed Cryoglobulinemiamentioning
confidence: 99%